Carbonized polydopamine nanoparticle reinforced graphene films with superior thermal conductivity. (August 2019) - Zou, Rui; Liu, Feng; Hu, Ning; Ning, Huiming; Jiang, Xiaoping; Xu, Chaohe; Fu, Shaoyun; Li, Yuanqing; Zhou, Xiaoyuan; Yan, Cheng
Abstract: Electronic components are becoming miniaturized and complicated, leading to increased levels of heat generation. Developing lightweight and ultrathin materials with superior thermal conductivity is urgently required to improve thermal management. Here, graphene films (GFs) were fabricated by vacuum filtration of graphene oxide-polydopamine (GO-PDA) solutions and graphitization of the obtained GO-PDA films. In the GO-PDA films, the GO sheets were crosslinked and reduced by PDA. Graphitization transformed PDA into carbonized PDA nanoparticles (CPDA NPs) with the crystal structure of nanosized graphites. The graphene sheets of GFs were covalently crosslinked and reinforced by the CPDA NPs to acquire a dense and flat structure with good sheet alignment and high density, rendering CPDA NP-reinforced GFs with a tensile strength of 47 MPa, an electrical conductivity of 0.89 × 10 6 S m −1, and a high thermal conductivity of 1584 W m −1 K −1 . In comparison, the GFs without the PDA only have a tensile strength of 6.4 MPa, an electrical conductivity of 0.30 × 10 6 S m −1, and a thermal conductivity of 244 W m −1 K −1 . Graphical abstract: Image 1